Novel in vitro evidence on the beneficial effect of quercetin treatment in vascular calcification - Ceccherini, E.; Gisone, I.; Persiani, E.; Ippolito, C.; Falleni, A.; Cecchettini, A.; Vozzi, F. (Frontiers in Pharmacology, 2024)
Vascular calcification is a pathological chronic condition characterized by calcium crystal deposition in the vessel wall and is a recurring event in atherosclerosis, chronic kidney disease, and diabetes. The lack of effective therapeutic treatments opened the research to natural products, which have shown promising potential in inhibiting the pathological process in different experimental models. This study investigated the anti-calcifying effects of Quercetin and Berberine extracts on vascular smooth muscle cells (VSMCs) treated with an inorganic phosphate solution for 7 days. Quercetin has shown the highest anti-calcifying activity, as revealed by the intracellular quantitative assay and by morphological analysis. Confocal microscopy revealed a downregulation of RUNX2, a key marker for calcified phenotype, which was otherwise up-regulated in calcified VSMCs. To investigate the antiinflammatory activity of Quercetin, culture media were subjected to immunometric assays to quantify the levels of IL-6 and TNF-α, and the caspase-1 activity. As expected, calcified VSMCs released a large quantity of inflammatory mediators, significantly decreasing in the presence of Quercetin. In summary, our findings suggest that Quercetin counteracted calcification by attenuating the VSMC pathological phenotypic switch and reducing the inflammatory response. In our opinion, these preliminary in vitro findings could be the starting point for further investigations into the beneficial effects of Quercetin dietary supplementation against vascular calcification.